Antibacterial Activity of Ethyl Acetate Extract of Beetroot (Beta vulgaris L.) against Methicillin-Resistant Staphylococcus aureus and Streptococcus mutans - Hariman, Hariman; Maimunah, Siti; Marbun, Eva Diansari; Asfianti, Vivi (CV. Nusantara Scientific Medical, 2025)
Beetroot (Beta vulgaris L.) is a cultivated plant with medicinal properties, containing bioactive compounds such as flavonoids, tannins, and saponins that are known to exhibit antibacterial activity. Methicillin-Resistant Staphylococcus aureus (MRSA) and Streptococcus mutans pose significant clinical challenges due to antibiotic resistance and their association with nosocomial infections and dental caries, respectively. This study aimed to evaluate the antibacterial activity of ethyl acetate extract of beetroot against MRSA (ATCC 43300) and Streptococcus mutans (ATCC 25175) using the disc diffusion method. Simplicia characterization revealed a water content of 13.15%, water-soluble extract of 42.5%, ethanol-soluble extract of 44.8%, total ash of 12.56%, and acid-insoluble ash of 1.81%. Phytochemical screening confirmed the presence of alkaloids, flavonoids, terpenoids, steroids, saponins, and tannins. Antibacterial testing at concentrations of 125, 250, and 500 mg/ml showed inhibition zones of 8.3, 8.7, and 11.5 mm against MRSA, and 7.5, 8.4, and 10.3 mm against S. mutans, respectively. The minimum inhibitory concentration (MIC) was determined to be 125 mg/ml for both bacterial strains. These findings suggest that the ethyl acetate extract of beetroot possesses promising antibacterial activity ranging from moderate to strong category.